Heterotrophically Ultrahigh-Cell-Density Cultivation of a High Protein-Yielding Unicellular Alga Chlorella With a Novel Nitrogen-Supply Strategy - Quan Xu (Frontiers Media S.A., 2021)
The unicellular green alga Chlorella is an ideal protein source. However, the high production cost and low production capability of the current main photoautotrophic culture mode limit its application especially as an alternative protein source for food and feed, which might be overcome through high-cell-density cultivation in fermenters. In this study, a Chlorella sorokiniana strain CMBB276 with high protein content was selected from five Chlorella strains by comprehensive evaluation of their growth rates, protein contents, and yields. The optimal cultural temperature, pH, and mole ratio of carbon and nitrogen (C/N) for C. sorokiniana CMBB276 growth were found to be 30°C, 6.5, and 18, respectively. Ammonium chloride was proved to be the best nitrogen (N) source for C. sorokiniana CMBB276 growth, whereas growth inhibition caused by the accumulation of salts was observed under fed-batch cultivation when maintaining a constant C/N ratio of 18 by controlling pH with sodium hydroxide solution. By simultaneously reducing the concentration of ammonium chloride in the feeding medium and controlling pH with ammonium hydroxide, we finally achieved the ultrahigh-cell-density cultivation of C. sorokiniana CMBB276. The highest biomass concentration and protein yield reached 232 and 86.55 g l−1, respectively, showing the great potential of culturing C. sorokiniana CMBB276 in fermenters for economic and large-scale protein source production.